THE SYNTHESIS OF PAINTING AND MUSIC: WASSILY KANDINSKY – ALFRED SCHNITTKE - Zavadska, Galina; Bagele, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The interaction between colors and sounds, music and painting has existed long since. Throughout the centuries these two kinds of art have been developing simultaneously and in close contact with each other, besides. Composers, especially those of the 20th century, find in the sphere of painting images for their musical compositions, without trying to depict definite plot lines or specific landscape sketches. The paper analyzes a specific composition by Alfred Schnittke – Wassily Kandinsky – The Yellow Sound. Research aim: to investigate the features of musical implementation of W. Kandinsky’s ideas by Alfred Schnittke on the basis of a comparative analysis of specific compositions of both authors. Research method: a comparative analysis